Cytotoxic effect and antioxidant activity of Andean berry (Vaccinium meridionale Sw) wine (2016)
ABSTRACT: Vaccinium meridonale Sw or Andean berry has antioxidant properties due to its high content of polyphenols, as anthocyanins and phenolic acids. Polyphenols have been associated with the prevention of chronic and cardiovascular diseases. In the last years, alcoholic drinks have been studied for their composition and health benefits. By this, the aim of this research was to obtain three types of alcoholic beverages from Andean berry, which have different treatments. The methods used to obtain the beverages were macerated fruit machine (MAC), preheating of the fruit (CAL) and by combining both of them (MIX). The antioxidant activity was evaluated by FRAP, DPPH, ORAC methods and anthocyanins and total phenols were measured. Finally, the antiproliferative effect was evaluated on a colon cancer cell line (SW480). Findings suggest that ethanol content of final products is not altered by treatment of unfermented Andean berry juice (must). The alcohol concentrations for MAC, CAL and MIX drinks were 90±1.7, 89±3.6 and 94±4.1 g/L, respectively. The results showed that CAL and MIX methods favor the extraction of secondary metabolites and consequently increase the antioxidant activity. The fermentation process affected the antioxidant power and total phenolic content in beverages CAL and MIX. However, no significant changes in these parameters were observed in the MAC drink. These beverages can eventually reduce the cancer cell viability between 15.1 (20 μg/L) and 37.2% (200 μg/mL). Thus, it was concluded that MIX treatment has higher antioxidant power and it could reduce the cancer cell viability.